With or Without You: Beneficial and Detrimental Associations Between Companion Dogs and Human Psychological Adjustment During a COVID-19 Lockdown Phase. (3rd September 2022) - Lima, Mariely; Mateus, Teresa Letra; Silva, Karine
ABSTRACT: It has been proposed that companion animals, and dogs in particular, may be helpful during the COVID-19 pandemic, notably for psychological adjustment. The present study addressed this idea in a sample of 509 Portuguese individuals exposed to a national lockdown. Linear regression analyses were performed to test for associations between having lived with a dog during that phase and experienced levels of anxiety and depression while considering potential moderating effects. Sub-analyses on 345 dog owners were performed to explore how different dimensions of the dog–owner relationship are associated with owners' anxiety and depression levels. A complex association was found between having lived with a dog during the lockdown, living area, and anxiety. For participants in rural and semi-urban areas, living with a dog was associated with lower anxiety; for participants in urban areas, living with a dog was associated with higher anxiety. Among dog owners, dog walking was marginally associated with lower depression, while perceived costs derived from caring for a dog and emotional closeness were associated with higher anxiety and depression. The results highlight the importance of going beyond mere ownership when studying the effects of companion dogs on human health and wellbeing. Also, they call for attention to dogs as a source of both concern and potential for health planners when defining strategies to manage mental health.